Political connections and corporate social responsibility reporting in Portugal - Bianchi, T.; Monteiro, P.; Azevedo, G.; Oliveira, J.; Viana, R.; Branco, M. (Journal of Financial Crime, 2019)
This paper examines the relation between firms’ political connections and corporate social responsibility (CSR) reporting in Portugal. We argue that in settings where the existence of political connections are viewed as damaging collective interests of stakeholders, political connected firms can deal with legitimacy issues from such connections by resorting to CSR practices and the reporting thereof. Using archival data from a panel sample of 36 firms from Portugal between 2009 and 2012, we examine the relation between political connections and CSR reporting by way of regression analysis. We find a positive relation between political connections and CSR reporting. This study draws on legitimacy theory to highlight that CSR can be used to deal with stakeholder activism and vigilance pertaining to suspicion related to the existence of political connections.